Sistem Informasi Absensi Guru Dan Siswa Berbasis Web dengan QR Code SD Briliant Islamic School - Willyansah; Aziz, Syarfi; Syahrul (Universitas Islam Balitar, 2024)
Technology is currently developing very rapidly. One of them is the use of attendance information systems in schools. At SD Briliant Islamic School, the current attendance system is still not computerized properly, namely by using an attendance check lock and problems that occur when recording data include incorrect data recording and taking a long time to record data. The aim of this research is to create a website-based teacher and student attendance system using a QR Code to expedite all attendance processes and the preparation of required reports from SD Briliant Islamic School. This attendance system has 2 users, namely superadmin and teacher. The method used is UML design, interviews and literature study. The results of this research are a website-based attendance system using QR Code and can meet attendance needs in real time and attendance recording can be done efficiently and reduces errors that occurred in the old system.